2020
DOI: 10.3390/joitmc6040169
|View full text |Cite
|
Sign up to set email alerts
|

Social-Media Analysis for Disaster Prevention: Forest Fire in Artenara and Valleseco, Canary Islands

Abstract: This manuscript investigates the use of social media, specifically Twitter, during the forest fires in Artenara and Valleseco, Canary Islands, Spain, during summer 2019. The used methodology was big-data analysis through the Union Metrics and Twlets tools, as well as content analysis of posts related to the fires written by seven relevant accounts on the days when the fires were active, which was between 17 August and 26 September, when 9636.40 hectares were burned. The accounts selected for analysis were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…In this regard, Zamarreño-Aramendia et al [10] believe that the context in which social media can be used for open innovation still needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, Zamarreño-Aramendia et al [10] believe that the context in which social media can be used for open innovation still needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…From a more practical perspective, Howe [61] suggests to public administrations to use open innovation and corporate R&D to fix issues in the communication and prevention of natural disasters. In such a framework, the use of social networks (and of Twitter, especially) should enable public officials to collect "knowledge produced by different involved stakeholders, as well as to use all these knowledge synergies in order to establish mid-and long-term prevention public policies" [10] p. 13. Against the background of a natural disaster, the data collection and processing described in this paper could be reduced from a daily to few hourly intervals in order to be able to obtain timely information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the results showed that slightly more than a half of the respondents had experience with the hydrant network, but it was not determined how they used it and whether it was done in a proper and safe way (Coar et al, 2020). The fact is that the fire cannot be absolutely prevented, but by taking various preventive measures, establishing regular inspection processes, regular servicing and maintenance of fire protection systems, correct and regular updating of procedures, instructions and other internal acts, which provide fire protection, it is possible to reduce consequences in case of fire (Crosby, 1905;Daane & Toth, 2005;Diamantes & Jones, 2020;Fan et al, 2020;Fuller, 1991;Mallonee et al, 1996;Zamarreño-Aramendia et al, 2020). Therefore, it is extremely important that the person entrusted with fire protection is informed about the measures and steps taken in case of fire protection.…”
Section: Discussionmentioning
confidence: 99%